Physicians' perception of their medical college. Issue 6 (12th June 2018) - Wilson, John; Talbot, Anthony
Abstract: The relevance of medical colleges has been questioned and their ability to respond to members' needs and system failures is unknown. We hypothesise that members believe that medical colleges are relevant to the current health agenda. We conducted a survey by email to determine satisfaction with the current state of the Royal Australasian College of Physicians (RACP) relevance and tested agreement with suggestions for change. We found that of 21 000 survey links sent, 13.1% of addressees replied. When questioned regarding the current state, less than 50% of respondents agreed with any of eight positive statements. Over two thirds supported involvement in policy and advocacy, as well as the use of digital plebiscites to express their views. Clarity around the use of members' subscriptions and value for money had the lowest scores. Of importance was the expression of need for a medical college (71%) and the finding that 58% of respondents would give more time to the RACP if asked. Of all respondents, 22% provided written comments that closely reflected scores on categorical questions. We conclude that, despite reported disengagement and lack of support for the current state, the majority of respondents to a survey of relevance believed in the need for a medical college.